(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
DNA profiling has attained a pivotal role in forensic identification. It has assumed great significance in terms of exclusion as well as fixation of identity and is being relied upon by law enforcers and judiciary equally. A study was conducted to look at the effect of temperature on blood samples for isolation of DNA at MNL Medical College, Allahabad, U.P. With the increase in temperature yield of DNA decreases in both fresh and dried blood samples. Fresh samples stored at -20°C,0°C,4°C,40°C had 2.38% ,3.47%, 10.19%, 13.79% and dried blood samples had 0.78%, 0.96%, 2.56%, 5.90% decrease in DNA yield after one week.